If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2(5) = -9 Multiply 2 * 5 y + 10 = -9 Reorder the terms: 10 + y = -9 Solving 10 + y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + y = -9 + -10 Combine like terms: 10 + -10 = 0 0 + y = -9 + -10 y = -9 + -10 Combine like terms: -9 + -10 = -19 y = -19 Simplifying y = -19
| y+2(2)=-9 | | kx^2-10x+25=0 | | -4y+2y=2y-6+y | | 49v^4-16t^2=0 | | y=-6(1) | | y=-6(0) | | y=-6(-1) | | y=-2(-6)-6 | | y=-2(-9)-6 | | 6(2x-8)=24x | | f(a+2)=a+2+3 | | f(0)=(0)+3 | | 12(7.5-1y)+6y=72 | | 4+(-3)*2= | | 4x+4x=30 | | 26+31=22x+59 | | 6(6-6y)+15y=90 | | f(5)=(5)+3 | | f(-8)=-8+3 | | f(0)=0+3 | | f(2a)=2a+3 | | 12x+6y-6y=72-6y | | (x+8)(x+2)=55 | | 5w-10=6w+9 | | 2a(5+7)= | | r^2+2r+3=0 | | -8x^2+x-16=10x^2-10 | | -5x^2+11x-6=0 | | .089=.0269+x | | -4x^2-5x=-6 | | y=-2x^3+2 | | -x=9x^2-10 |